INFLUENCE OF LOCAL APARTMENT REGULATION OF HOUSEHOLD HEATING SYSTEMS ON ENERGY CONSUMPTION - Дешко, Валерій; Білоус, Інна; Максименко, Олександра (Technologies and Engineering, 2022)
Target. Analysis of the distribution of thermal energy costs for heating typical buildings before and after thermal modernization, taking into account local apartment-by-apartment regulation, as well as a study of the impact of heat flows between adjacent areas (apartments). Methodology. Analysis of the distribution of thermal energy costs for heating typical buildings before and after thermal modernization, taking into account local apartment-by-apartment regulation, as well as a study of the impact of heat flows between adjacent areas (apartments). Results. The influence of internal heat flows to adjacent rooms, change of internal air temperature under the influence of local change of flow coefficients in the heater is investigated. Scientific novelty. The influence and limitations of local heating control of vertical single-pipe systems in the conditions of thermal interaction of the room with adjacent areas of the building before and after thermal modernization of the building are shown. Practical significance. Developed approaches, the results obtained on the influence of local control of vertical single-pipe heating systems can be used to clarify the distribution of energy consumption for heating between individual areas of apartment buildings.